NMR absolute shielding scale and nuclear magnetic dipole moment of 207Pb. Issue 24 (6th June 2016) - Adrjan, Bożena; Makulski, Włodzimierz; Jackowski, Karol; Demissie, Taye B.; Ruud, Kenneth; Antušek, Andrej; Jaszuński, Michał
Abstract : A new absolute shielding scale is proposed for 207 Pb nuclear magnetic resonance (NMR) spectroscopy. Abstract : An absolute shielding scale is proposed for 207 Pb nuclear magnetic resonance (NMR) spectroscopy. It is based on ab initio calculations performed on an isolated tetramethyllead Pb(CH3 )4 molecule and the assignment of the experimental resonance frequency from the gas-phase NMR spectra of Pb(CH3 )4, extrapolated to zero density of the buffer gas to obtain the result for an isolated molecule. The computed 207 Pb shielding constant is 10 790 ppm for the isolated molecule, leading to a shielding of 10799.7 ppm for liquid Pb(CH3 )4 which is the accepted reference standard for 207 Pb NMR spectra. The new experimental and theoretical data are used to determine μ ( 207 Pb), the nuclear magnetic dipole moment of 207 Pb, by applying the standard relationship between NMR frequencies, shielding constants and nuclear moments of two nuclei in the same external magnetic field. Using the gas-phase 207 Pb and (reference) proton results and the theoretical value of the Pb shielding in Pb(CH3 )4, we find μ ( 207 Pb) = 0.59064 μ N . The analysis of new experimental and theoretical data obtained for the Pb 2+ ion in water solutions provides similar values of μ ( 207 Pb), in the range of 0.59000–0.59131 μ N .